The associations between mindfulness, metacognition and HbA1c levels among diabetic pregnant patients: A case control study - Gölbaşı Ceren; Çökmüş Fikret Poyraz; Mustoo Başer Lejla; Gölbaşı Hakan; Ünal Aydın Pınar; Aydɪn Orkun (Psihologija)
Pregnancy, due to the diversity of lifestyle changes it leads to, may represent a period characterized by intensified stress. Women of childbearing age are at the highest risk for a number of health difficulties and complications, including glucose abnormalities. Such an occurrence often has a set of complex consequences for both the mother and the newborn. We aimed to examine how mindfulness and metacognition interact with HbA1c levels during pregnancy characterized by Gestational diabetes mellitus (GDM). One hundred pregnant women with GDM and ninety-eight healthy pregnant women were enrolled in the study. Average blood glucose levels were assessed by HbA1c monitoring. Participants completed the Hospital Anxiety and Depression Scale (HADS), DSM-5 Level 2-Anxiety- Adult measure (DSM-5 Anxiety), Five-Facet Mindfulness Questionnaire (FFMQ), and Metacognition Questionnaire-30 (MCQ-30). A negative correlation was found between HbA1c and FFMQ “Describing” subtest, while a positive correlation was obtained between HbA1c and MCQ-30 “Negative beliefs about uncontrollability and danger” subtest. Multiple linear regression showed an association between Mindfulness Describing subtest and HbA1c as an outcome variable. Findings imply the association between mindfulness and HbA1c during pregnancy period. Mindfulness cultivation seems to be relevant in emotional and cognitive processes in order to minimize negative stress related effects on well– being during pregnancy. Such approach may be beneficial in promoting treatment compliance among pregnant women with diabetes, but also among women experiencing low prenatal well– being.